Active learning: engaging students in the classroom using mobile phones - Ayu, Media Anugerah; Taylor, Ken; Mantoro, Teddy (2009)
Audience Response Systems (ARS) are used to achieve active learning in lectures and large group environments by facilitating interaction between the presenter and the audience. However, their use is discouraged by the requirement for specialist infrastructure in the lecture theatre and management of the expensive clickers they use. We improve the ARS by removing the need for specialist infrastructure, by using mobile phones instead of clickers, and by providing a web based interface in the familiar Wikipedia style. Responders usually vote by dialing and this has been configured to be cost free in most cases. The desirability of this approach is shown by the use the demonstration system has had with 21,000 voters voting 92,000 times in 14,000 surveys to date.